Screening of Prognostic Biomarkers for Stereotactic Body Radiation Therapy in Primary Liver Cancer - Zhenzhen Liang PhD; Chang Xue MS; Qing Chen MS; Mengke Li MS; Guanghui Li MS; Hao Feng MS; Yi Liu MS; Xiaodong Liu PhD; Shumei Ma PhD (SAGE Publishing, 2022)
Objective So far there are still no effective immediate-early markers for assessing the efficacy of Stereotactic Body Radiation Therapy (SBRT). To find effective biomarkers for accurate assessment of the efficacy of SBRT in patients with primary liver cancer, we conducted this study including retrospective part and prospective part. Material and Methods 589 patients with primary liver cancer were included at Ruikang Hospital affiliated to Guangxi Medical University from January 2012 to December 2018. Follow-up was conducted, clinical information and a total of 17 patients with 51 blood samples (before SBRT, before discharge and 2 months after SBRT) were collected. mRNAs profiles on 2 patients with 6 blood samples were detected by high-throughput sequencing, followed by qPCR verification on 15 patients with 45 blood samples. Results The commonly used serum biomarkers such as AFP, CEA, and CA125 shown low prognostic value in distinguishing survival group and death group, indicated by low AUC (less than .7) and Youden indexes (less than .5). Based on high-throughput sequencing of test group and qPCR detection of another verification group, we found 16 up-regulated and 12 downregulated genes after SBRT. Among them, ADIPOR1 and EPB42 showed significantly different between effective and ineffective group after SBRT, ROC suggested that based on the optimal threshold of .5838, ADIPOR1 shown a sensitivity of 100% and a specificity of 83.33% to distinguish effective from ineffective group. And EPB42 had a sensitivity of 75% and a specificity of 100% at the optimal threshold of 1.3817. In addition, GSEA showed that high expression of ADIPOR1 was mainly related to Mismatch repair, Circadian rhythm, Protein processing in endoplasmic reticulum, DNA replication, and Fanconi anemia pathways. Conclusion ADIPOR1 in whole blood is a promising candidate to act as prognostic biomarker for predication of SBRT outcomes in primary liver cancer patients.